Uracilato and 5-halouracilato complexes of Cu(II), Zn(II) and Ni(II). X-ray structures of [Cu(uracilato-N1)2(NH3)2]·2(H2O), [Cu(5-chlorouracilato- N1)2(NH3)2](H2O)2, [Ni(5-chlorouracilato-N1)2(en) 2]·2H2O and [Zn(5-chlorouracilato-N1)(NH3)3]·(5-chlorouracilato-N 1)·(H2O) - Terrón, A. (2004)
Four new complexes of uracilato and 5-halouracilato with the divalent metal ions Cu(II), Zn(II) and Ni(II) were obtained and structurally characterized. [Cu(uracilato- N1)2(NH3) 2]·2(H2O) (1) and [Cu(5-chlorouracilato-N 1)2(NH3)2](H2O) 2 (2) complexes present distorted square planar co-ordination geometry around the metal ion. Although an additional axial water molecule is present [Cu(II)-OH2=2.89 Å (for 1) and 2.52 Å (for 2)] in both cases, only in the complex 2 would be considered in the limit of a bond distance. The Zn(II) in [Zn(5-chlorouracilato-N1)(NH 3)3]·(5-chlorouracilato-N1) ·(H2O) presents a tetrahedral co-ordination with three ammonia molecules and the N1 of the corresponding uracilato moiety. A non-coordinated uracilato molecule is present as a counterion and a recognition between co-ordinated and free ligands, by means a tandem of H-bonds, should be mentioned. Finally, the complex [Ni(5-chlorouracilato-N 1)2(en)2] (H2O)2 (where en is ethylenediamine) presents a typical octahedral trans co-ordination with additional hydrogen bonds between 5-chlorouracilato and the NH2 groups of ethylenediamine units.